2016
DOI: 10.1017/s030500091500080x
|View full text |Cite
|
Sign up to set email alerts
|

Early child L2 acquisition: Age or input effects? Neither, or both?

Abstract: This paper explores whether there is evidence for age and/or input effects in child L2 acquisition across three different linguistic domains, namely morphosyntax, vocabulary, and syntax-semantics. More specifically, it compares data from English-speaking children whose age of onset to L2 Dutch was between one and three years with data from children whose age of onset was between four and seven years in their acquisition of verb morphology, verb placement, vocabulary, and direct object scrambling. The main find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 53 publications
5
62
0
6
Order By: Relevance
“…This means that what is relevant for maintaining stable knowledge of German morphology is not the age at which the speakers started to acquire German, but for how long they were exposed to it. AoA in early childhood (up to age 4), per se, does not predict the bilingual speakers’ outcome, which is, instead, mainly modulated by effects of timing of acquisition (Schulz & Grimm, ) and by accumulated amount of exposure over time (Unsworth, ). Schulz and Grimm (), for instance, show that instances of protracted development of early acquired phenomena in children exposed to L2 German by age 3 disappear within a short period of time (before age 6), whereas regarding late acquired phenomena (case marking and sentential negation, in their study), simultaneous and early sequential bilingual children in preschool age do not differ.…”
Section: Discussionmentioning
confidence: 99%
“…This means that what is relevant for maintaining stable knowledge of German morphology is not the age at which the speakers started to acquire German, but for how long they were exposed to it. AoA in early childhood (up to age 4), per se, does not predict the bilingual speakers’ outcome, which is, instead, mainly modulated by effects of timing of acquisition (Schulz & Grimm, ) and by accumulated amount of exposure over time (Unsworth, ). Schulz and Grimm (), for instance, show that instances of protracted development of early acquired phenomena in children exposed to L2 German by age 3 disappear within a short period of time (before age 6), whereas regarding late acquired phenomena (case marking and sentential negation, in their study), simultaneous and early sequential bilingual children in preschool age do not differ.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence comes from (mostly) parental reports of children's naturalistic bilingual exposure involving samples of children along varying onsets of bilingual exposure within the first 4 to 7 years of life. Unsworth (), for example, inspected linguistic outcomes in Dutch as a majority language among English–Dutch speaking children who had had an onset of bilingualism between 2 and 5 years of age and were tested between ages 7 and 9. She found that the contribution of age of bilingual onset was not predictive of linguistic outcomes “[o]nce age at testing, (cumulative) length of exposure, and current amount of exposure were controlled for” (p. 626).…”
Section: Measuring Input and Exposure During Childhood: Possible In Hmentioning
confidence: 99%
“…Regarding child second language (cL2) acquisition, morphological acquisition has received more attention than the development of syntax. Furthermore, existing studies on cL2 complex syntax examine comprehension rather than production (e.g., Unsworth, 2016). Consequently, the developmental patterns and mechanisms of syntactic production in cL2 learners of English are largely unknown.…”
mentioning
confidence: 99%